Pembelajaran Dolanan Jawa Berbasis Pilar-pilar Pendidikan bagi Anak Usia Dini - Budi Raharja (Institut Seni Indonesia Yogyakarta, 2020)
The pillars of education (knowledge, skills, social or cooperation, individual, and spiritual) are used as media to expand the achievements of Javanese dolanan learning, which generally focus on social-emotional aspects only. The results of this study are expected to be used as a reference for stakeholders, especially Kindergarten teachers, as a medium for teaching Javanese dolanan to create a generation who is knowledgeable, has adequate skills, and has a high social spirit, and humble and obedient to worship as well. The experimental research method was used in this study to test the application results. In contrast, the research design is Single Subject Research (SSR) or single subject (group) which functions as an intervention group and a control group to test the intervention results. The research was carried out at Pertiwi 3 Kindergarten, Sinduadi, Mlati, Sleman Yogyakarta by giving a group of school students training to play Javanese dolanan entitled recreation, accompanied by children’s gamelan for six months (twice a week). After having the treatment, their behaviour changes were identified, calculated, and grouped based on the respective development field groups. As a result, Javanese dolanan learning based on educational pillars contains development aspects of the physical, motoric, cognitive, language, artistic, and children social-emotional. In contrast, the number of development materials includes 60 learning development materials.